Catalytic Intermediate Crystal Structures of Cysteine Desulfurase from the Archaeon Thermococcus onnurineus NA1. (24th April 2017) - Ho, Thien-Hoang; Huynh, Kim-Hung; Nguyen, Diem Quynh; Park, Hyunjae; Jung, Kyoungho; Sur, Bookyo; Ahn, Yeh-Jin; Cha, Sun-Shin; Kang, Lin-Woo
Abstract : Thermococcus onnurineus NA1 is an anaerobic archaeon usually found in a deep-sea hydrothermal vent area, which can use elemental sulfur (S 0 ) as a terminal electron acceptor for energy. Sulfur, essential to many biomolecules such as sulfur-containing amino acids and cofactors including iron-sulfur cluster, is usually mobilized from cysteine by the pyridoxal 5′-phosphate- (PLP-) dependent enzyme of cysteine desulfurase (CDS). We determined the crystal structures of CDS from Thermococcus onnurineus NA1 (ToCDS), which include native internal aldimine (NAT), gem-diamine (GD) with alanine, internal aldimine structure with existing alanine (IAA), and internal aldimine with persulfide-bound Cys356 (PSF) structures. The catalytic intermediate structures showed the dihedral angle rotation of Schiff-base linkage relative to the PLP pyridine ring. The ToCDS structures were compared with bacterial CDS structures, which will help us to understand the role and catalytic mechanism of ToCDS in the archaeon Thermococcus onnurineus NA1.